Controlled trial of oral channa striatus extract and glucosamine sulphate among primary knee osteoarthritis patients - Ling, Bong Hoi (2016)
Background Knee osteoarthritis is the commonest form of arthritis worldwide with significant impact on the health-related quality of life. Complementary and alternative medicine use in osteoarthritis is gaining popularity. Channa striatus, an indigenous fresh water fish in Malaysia is well-known for its nutritional and medicinal value in traditional medicine. The current evidences support its therapeutic potential in treating primary knee osteoarthritis patients. Objectives The aim of the study was to compare the effectiveness of oral Channa striatus extract and Glucosamine sulphate in improving knee symptoms and physical function, as well as in rescue analgesic consumption among primary knee osteoarthritis patients. Methods Seventy eight patients with primary knee osteoarthritis were enrolled into this doubleblind randomized controlled trial and assigned to receive either Channa striatus 500 mg/day (n = 39) or Glucosamine sulphate 1500 mg/ day (n = 39) for six months. The efficacy outcome measures were Western Ontario and Mc Master Osteoarthritis Index WOMAC index for pain, stiffness and physical function, Visual Analogue Scalefor pain during movement and Analgesic score for rescue analgesia consumption. These outcomes measures were assessed using an intention-to-treat analysis. All patients were evaluated at baseline, 3 and 6 months post randomization. Results All the baseline characteristics were comparable between Channa striatus and Glucosamine sulphate group. Of 78 patients randomized, 73 completed the study (Channa striatus, n = 36 and Glucosamine sulphate, n = 37). There were no statistically significant difference between these two groups in WOMAC index, Visual Analogue scale and Analgesic score after 6 months of intervention. However, there were statistically significant improvement in all the domains of WOMAC index based on time for Channa striatus group from baseline to 3 months up to 6 months. Although there were improvement observed from 3 to 6 months of treatment, they were not statistically significant. All the safety profile parameters were normal for both groups before and after the intervention. Conclusions Channa striatus 500 mg/ day is comparable to Glucosamine sulphate 1500 mg/ day in improving pain, stiffness and physical function in patients with primary knee osteoarthritis. It could be a new alternative treatment with good safety profile for medium to long term management of knee osteoarthritis.